Comparative evaluation of 2% sodium fluoride iontophoresis and other cavity liners beneath silver amalgam restorations - Gupta M; Pandit I; Srivastava N; Gugnani N (Wolters Kluwer Medknow Publications, 2010)
Background: This study was designed to compare 2% sodium fluoride (NaF) iontophoresis with other cavity liners. Materials and Methods: This study was carried out in 30 patients in the age group 10-14 years with bilateral carious permanent first molars. The study evaluated the use of 2% NaF iontophoresis as a cavity liner and also compared its desensitizing effect with varnish and an adhesive bonded liner. Sensitivity gradings were done on a subjective verbal rating scale. Results: All the liner treatments decreased the sensitivity following liner application. However, decrease of sensitivity in the case of 2% NaF iontophoresis was more compared with that of varnish and adhesive bonded liner. The results were statistically significant. Conclusions: It was found that 2% NaF iontophoresis was more effective in reducing the postoperative sensitivity compared with that of varnish and scotchbond multipurpose.